PELATIHAN TEKNOLOGI FERMENTASI KOMBINASI FESES SAPI DAN BABI DALAM DIGESTER MOBILE SEBAGAI UPAYA PRODUKSI BIOENERGI ALTERNATIF - Suryatika, Suryatika; Dalem, R.; Simpen, N.; Miwada, N. S. (Buletin Udayana Mengabdi, 2012)
Has done community service in order to provide the knowledge and skills to members of a group of cattle in the village of Pengotan, Bangli about how processing cow manure and pig waste into biogas, as an environmentally friendly alternative energy. Method of activities with demoplot how to create installations, mobile digester, which is a fermentation tank where the cow and pig feces to produce biogas (bioenergy) is ready to use. The group of farmers who participated in the training activities of household-scale biogas production is very enthusiastic follow until the end. Almost 100% of participants acknowledged that mobile digester offered as a place of production of biogas can be accepted and become the solution of cultural problems that have been developed in rural areas Pengotan.